(untitled) (Tanzania Journal for Population studies and Development, 2025)
This study examines digital literacy skills among librarians in university libraries in Tanzania, focusing on skill levels, acquisition methods, and gender influence. A descriptive research design, integrating qualitative and quantitative research approaches, was employed. A sample of 212 librarians was selected through simple random sampling, while five library directors were chosen purposively. Data collection involved questionnaires, interviews, and observations; and the data were analysed using SPSS, (version 20). The findings indicate that most librarians demonstrate moderate competence in online searching, library management systems, and word processing; but struggle with video conferencing. Formal training, including structured programmes, workshops, and seminars, are the primary method of skill acquisition; with self-learning playing a supplementary role. Gender does not significantly influence digital skills acquisition, as shown by a correlation coefficient of r=0.007 and a significance level of p=0.923. To bridge the gaps, the study recommends targeted training on video conferencing tools, and expanding structured training through collaboration with professional bodies like the COTUL. Moreover, ensuring equal access to digital literacy programmes and overcoming structural and financial challenges are crucial for sustained digital literacy development in university libraries.